Analysis and Development of Silvopasture Agroforestry System in Bangkalan District - Vadila Mulia Putri; Catur Putri Enggit Reksiana; Muhammad Arif Wahyudin; Laras Setyowati; Barna Deta Cristin Naftaly; Irfan Nurfaiq (Future Science, 2022)
Silvopasture is a land management system that combines forestry components with livestock components. A study on the analysis and development of the silvopasture agroforestry system was conducted in Bangkalan Regency, Madura in September 2022. The purpose of this study is to identify the components in silvopasture and the interactions between its components. In addition, identifying the role of silvopasture based on production and protection functions for agroforestry development is then made. The research was conducted in three stages: secondary data collection, field survey for primary data collection, and presentation of research results. The results showed that silvopasture was applied using a random mixture planting pattern that was grown in a monoculture. This agroforestry system combines the cultivation of teak, cattle, and chickens, and weeds under teak stands. The silvopasture has a role in improving soil fertility, reducing nutrient loss, increasing N availability, maintaining soil physical properties, reducing erosion hazards, creating a microclimate, reducing weed populations, and protection against plant disease pests. The development plan is prepared by taking into account the principles of productivity, sustainability, and adaptability (according to local conditions).